Unraveling Metacognitive Regulation in Physics: Mapping High School Students’ Skills using the Rasch Model - Putra, Ihsan Hijria; Novia, Hera; Muslim, Muslim; Sihombing, Rizky Agassy (Unnes Science Education Journal, 2025)
Metacognitive regulation skills are crucial in addressing increasingly complex global challenges. These skills enable individuals to comprehensively solve problems by managing their thinking strategies effectively. This study employs a descriptive approach and utilizes the Metacognitive Awareness Inventory, adapted from Schraw and Dennison’s work. The descriptive research involved 53 tenth grade students from a high school. The primary objective of this study is to map metacognitive regulation and their potential in tackling complex problems. Data analysis integrates Likert-scale results with percentage calculations for each as pect. Additionally, the data were analyzed to determine the reliability of the instrument, identify metacognitive regulation patterns, and map the distribution of students’ abilities using the Rasch model. The findings reveal variations in students’ metacognitive regulation achievements: Planning 82%, Information Management Strategies 73%, Comprehension Monitoring 77%, Debugging Strategies 82%, and Evaluation 92%. These indicate that students’ metacognitive regulation still require further development like Information Management Strategies. The conclusion of this research is students’ metacognitive regulation shows variation across domains and it has significant potential in helping to solve complex problems. This study underscores the importance of designing targeted instructional strategies to enhance students’ metacognitive regulation skills, ensuring they are better equipped to handle complex learning challenges.